2005
DOI: 10.1177/0169796x05054623
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Gender–Water Nexus in Rural Bangladesh

Abstract: This article presents a comprehensive analysis of the gender-water nexus in rural Bangladesh based on extensive field survey, focus group discussion, and interview with key informants, all carried out at seven study locations across Bangladesh. It presents the findings in four key areas: household water management, health and well-being, irrigation water management, and water related vulnerability. It has been observed that water for household use is collected by women and children, who face an array of physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 7 publications
(6 reference statements)
0
35
3
Order By: Relevance
“…3 The upazilas are the second lowest tier of regional administration in Bangladesh. 4 Farakka Barrage is a barrage across the Ganges River, located in the Indian state of West Bengal, roughly 16.5 kilometres from the border with Bangladesh. Construction was started in 1961 and completed in 1975 and this barrage has great impact on the tidal river flows and its management in Bangladesh.…”
Section: Water Scarcity In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The upazilas are the second lowest tier of regional administration in Bangladesh. 4 Farakka Barrage is a barrage across the Ganges River, located in the Indian state of West Bengal, roughly 16.5 kilometres from the border with Bangladesh. Construction was started in 1961 and completed in 1975 and this barrage has great impact on the tidal river flows and its management in Bangladesh.…”
Section: Water Scarcity In Bangladeshmentioning
confidence: 99%
“…Nowadays there is an increasing trend of water scarcity, which is one of the pressing challenges in different countries around the world. Problems that are related with water availability and water quality are increasing rapidly and have become particularly severe in developing countries, affecting not only the drinking water supply, but also sanitation, food security, economy and transport [4,5]. Water problems are not only related to availability or quality, but to water management, which is influenced by social conditions [6,7]., As stated by the World Water Forum of 2002, "It is a crisis of managing water so badly, that billions of people and the environment suffer badly and prospects at the longer term look like grim" [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, also from Bangladesh, Faisal and Kabir (2005) show how local cultural norms, such as purdah, and individual attributes, such as class and age, interact with the materiality of the water sources. For example, poorer women were more likely to collect water themselves than wealthy women, but water collection norms were also modified by the distance and public nature of the well, as well as arsenic contamination.…”
Section: Water Spaces and Gendermentioning
confidence: 91%
“…In Bangladesh, women have no involvement in agricultural water management. In the past, the 'right to water' was tied to the 'right to land,' which was usually in the hands of men (Faisal and Kabir 2005 ) . According to Zwarteveen and Meinzen-Dick ( 2001 ) , the insecure mechanisms that women have with which to negotiate water access can have a negative impact on the quality and distribution of this resource.…”
Section: Community Capitals From a Gender Perspectivementioning
confidence: 99%
“…Likewise, women are more vulnerable to ecological disasters that are now increasing in intensity and frequency due to the effect of climate change. Faisal and Kabir ( 2005 ) reported that women in Bangladesh identifi ed a number of waterrelated factors that make them more vulnerable on a daily or seasonal basis. Collecting drinking water becomes extremely diffi cult during fl ooding as well as during droughts when women may have to walk several kilometers just to fetch a pitcher of water.…”
Section: Community Capitals From a Gender Perspectivementioning
confidence: 99%